2017
DOI: 10.3390/su9050678
|View full text |Cite
|
Sign up to set email alerts
|

Toward Geodesign for Watershed Restoration on the Fremont-Winema National Forest, Pacific Northwest, USA

Abstract: Spatial decision support systems for forest management have steadily evolved over the past 20+ years in order to better address the complexities of contemporary forest management issues such as the sustainability and resilience of ecosystems on forested landscapes. In this paper, we describe and illustrate new features of the Ecosystem Management Decision Support (EMDS) system that extend the system's traditional support for landscape analysis and strategic planning to include a simple approach to feature-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…The first objective of the study was to prioritize LCUs within the study area (1) based on conditions that support the spread of large wildfires, (2) that have valuable resources nearby, (3) and that have good access to water points and escape routes (paths at least 3 m wide). In the context of spatial decision support, this phase of the analysis can be viewed as strategic prioritization insofar as we are attempting to spatially allocate MASSs, considering which are the high priority landscape units (Reynolds et al, 2017), given the above three criteria. The second objective, given the identification of MASSs under objective 1, was to identify which fuel treatments would be the most effective within high priority MASSs with respect to limiting potential fire intensity and allowing firefighters to work more efficiently and more safely during suppression activities.…”
Section: Conceptual Design Of the Planning Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…The first objective of the study was to prioritize LCUs within the study area (1) based on conditions that support the spread of large wildfires, (2) that have valuable resources nearby, (3) and that have good access to water points and escape routes (paths at least 3 m wide). In the context of spatial decision support, this phase of the analysis can be viewed as strategic prioritization insofar as we are attempting to spatially allocate MASSs, considering which are the high priority landscape units (Reynolds et al, 2017), given the above three criteria. The second objective, given the identification of MASSs under objective 1, was to identify which fuel treatments would be the most effective within high priority MASSs with respect to limiting potential fire intensity and allowing firefighters to work more efficiently and more safely during suppression activities.…”
Section: Conceptual Design Of the Planning Problemmentioning
confidence: 99%
“…The combination of accessibility, water supply and fuel management opportunities, in particular, was considered necessary to the allocation of MASSs to ensure that adequate levels of firefighter safety are achieved during fire suppression efforts. Our overall approach to the project employs a combination of strategic planning for spatially allocating MASSs on the landscape, and tactical planning to select priority management actions within individual MASS, for which we used the Ecosystem Management Decision Support (EMDS) system (Reynolds et al, 2003(Reynolds et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…There are some applications of prioritizing landscape restoration, using MCDA and EMDS. For example, Cannon et al [23] prioritized restoration areas for the development of stand treatments (e.g., forest tree thinning, prescribed fire), and Reynolds et al [24] identified the priority landscape units for treatment (e.g., restoration) and the priority treatment actions to be implemented there.…”
Section: Introductionmentioning
confidence: 99%
“…Reynolds et al [32] also illustrated a variety of analytical sequences for decision support involving assessment and strategic and tactical planning, but more generally the architecture of EMDS was extensively re-engineered at version 5.0 to support the concept of workflows, by which any of the EMDS analytical components described above can be invoked in any sequence(s) (or series of sequences) needed to support spatial analysis and planning. EMDS currently supports Microsoft Windows Workflow for creating, running, and monitoring scientific workflows and Workflow NET.…”
Section: Additional Steps In Decision Support For Ecosystem Restoratimentioning
confidence: 99%
“…In other words, the strategic question concerns where, while the tactical question concerns what. Reynolds et al [32] recently experimented with a CDP solution for tactical planning, however we believe that tactical decision models based on GeNIe and VisiRule may be more effective in tactical decisions, primarily because these systems can model more complex problems than CDP. For example, GeNIe supports sophisticated probabilistic reasoning based on Bayesian inference [33], and VisiRule, although providing a simple graphic interface, is supported by a powerful Prolog engine that allows very complex reasoning.…”
Section: Additional Steps In Decision Support For Ecosystem Restoratimentioning
confidence: 99%